'Deconstructionist' as the Role of a Teacher in Postmethod Pedagogy - Kamali, Hari C. (Technium Social Sciences Journal, 2021)
Postmethod pedagogy is the development in pedagogical practices after 1990s and is open to further developments as "a pedagogy in progress" (Kumaravadivelu, 2001). Implication of postmethod pedagogy underpinned by deconstruction has the potentials to make pedagogy more effective for which the postmethod teacher needs to play the role of a deconstructionist teacher. So in this paper I have reviewed the works on postmethod pedagogy and deconstruction and explored how they are interrelated and how they can be exploited as deconstructive pedagogy to make pedagogy more effective in context. As a result, it is concluded that when a postmethod teacher practices pedagogy as a deconstructionist teacher, any challenges emerging in the practice of pedagogy can be addressed as deconstructive pedagogy destabilizes the pedagogical practices and looks for possibilities of multiple meanings in context.